Pengaruh Daya Microwave terhadap Yield pada Ekstraksi Minyak Atsiri dari Bunga Kamboja (Plumeria Alba) menggunakan Metode Microwave Hydrodistillation - Erliyanti, Nove Kartika; Rosyidah, Elsa (Jurnal Rekayasa Mesin, 2017)
Frangipani oil is one of the most expensive essential oils. Conventional extraction methods has many disadvantages, so the microwave hydrodistillation method is used as an alternative to optimize the quality and quantity of frangipani oil. The purpose of this study was to investigate the effect of microwave power on the yield of frangipani oil. The research stage was carried out by inserting frangipani flower that has been cut into the flask and mixed with different aquadest solvent volumes of 300, 400, 500, and 600 ml. The flask put into the microwave with different powers of 300, 450, and 600 W for three hours. The resulting vapor is collected and separated in a separating funnel. The process is carried out at atmospheric pressure and the operating temperature is 100 Â°C. Finally, the yield percentage determined from resulting product. The results showed that microwave power had a significant effect on the yield percentage of frangipani oil. The yield percentage increased with increasing the microwave power. The highest yield percentage was generated at 600 Watt, 25 gram flower mass, and 600 ml volume, which was 1,612%.